A methodology for evaluating caving subsidence backfilling - Jakubec, J.; Hockley, D.; Lizcano, A.; Thomas, A.; Xu, Y.-H. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining methods – including block, panel, and sublevel caving – produce surface subsidence as ore extraction causes the cave to propagate upwards. When a sufficient volume of ore is extracted, initial elastic deformation turns into surface cracking and eventually a subsidence crater forms. As mining continues, this crater increases in size, both vertically and laterally. Deposition of fill in the crater is an effective method to limit crater expansion and the associated deformation or cracking of the surrounding ground. This paper outlines a comprehensive methodology for the technical and economic assessment of subsidence control by filling, including fill sources, deposition methods and related requirements, possible benefits for control of water ingress, sulphide oxidation and closure, and possible risks such as early dilution and/or inrushes to the extraction level.